2015
DOI: 10.1002/pssa.201431771
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting enrichment of arc discharge single‐walled carbon nanotubes by density gradient ultracentrifugation

Abstract: Due to their intrinsic properties, single‐walled carbon nanotubes (SWCNTs) are promising candidates for source‐drain channels in field‐effect transistors (FETs). However, their application in transistors requires semiconducting tubes, and thus, sorting of SWCNTs according to those. The basis for an efficient sorting is the dispersion of the material that usually includes but is not limited to applying tip sonication in the presence of appropriate amphiphilic molecules. We present a high semiconducting enrichme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Starting with the raw materials, CNTs can be synthesized via a variety of methods, including electric arc discharge, laser ablation, vaporization induced by a solar beam, catalytic chemical vapor deposition (CVD), plasma-enhanced CVD, laser-assisted CVD, and so on. Although some of these methods are highly energy-consuming, large-scale industrial manufacturing of CNTs with improved properties is realizable based on the facts that the production output reached ∼5 kiloton annually in 2011 and the estimated production output in 2022 will be >20 kiloton. , To obtain either metallic or semiconducting enriched CNT, a number of selective synthesis methods concerning controlling some vital factors, such as catalyst particles, carbon source, growth temperature, substrates, and other cotreatments, during the synthesis have been designed. In addition, the same diversity of nanotubes can also be obtained by post-growth purification, such as density-gradient ultracentrifugation, gel exclusion of surfactant-wrapped CNT, ion-exchange chromatography of DNA-wrapped CNT, UV irradiation, electrical breakdown, selective gas-phase plasma etching, and alternating current dielectrophoresis. , Recently, a novel separation method was developed to achieve high-purity single-chirality SWCNTs. Specifically, single-chirality SWCNTs were separated from the mixture by a given polymer two-phase system, in which ssDNA was used to wrap the SWCNT to form the hybrids sensitive to the slight differences in two phases.…”
Section: Preparation Of Transparent Cnt Filmsmentioning
confidence: 99%
“…Starting with the raw materials, CNTs can be synthesized via a variety of methods, including electric arc discharge, laser ablation, vaporization induced by a solar beam, catalytic chemical vapor deposition (CVD), plasma-enhanced CVD, laser-assisted CVD, and so on. Although some of these methods are highly energy-consuming, large-scale industrial manufacturing of CNTs with improved properties is realizable based on the facts that the production output reached ∼5 kiloton annually in 2011 and the estimated production output in 2022 will be >20 kiloton. , To obtain either metallic or semiconducting enriched CNT, a number of selective synthesis methods concerning controlling some vital factors, such as catalyst particles, carbon source, growth temperature, substrates, and other cotreatments, during the synthesis have been designed. In addition, the same diversity of nanotubes can also be obtained by post-growth purification, such as density-gradient ultracentrifugation, gel exclusion of surfactant-wrapped CNT, ion-exchange chromatography of DNA-wrapped CNT, UV irradiation, electrical breakdown, selective gas-phase plasma etching, and alternating current dielectrophoresis. , Recently, a novel separation method was developed to achieve high-purity single-chirality SWCNTs. Specifically, single-chirality SWCNTs were separated from the mixture by a given polymer two-phase system, in which ssDNA was used to wrap the SWCNT to form the hybrids sensitive to the slight differences in two phases.…”
Section: Preparation Of Transparent Cnt Filmsmentioning
confidence: 99%
“…Many studies demonstrated that a 3 : 2 or 4 : 1 ratio of SDS/SC could enrich high-purity m-SWCNTs while a 1 : 4 ratio of SDS/SC can enrich high-purity s-SWCNTs when their concentrations are around 1% w/v. 39,78,79 For realizing tight diameter distributions of s-SWCNTs, Seo et al reported a dual-iteration DGU method: initially using SC to purify raw materials and extract wellcoated SWCNT species followed by using the SDS/SC co-surfactant to isolate s-SWCNTs. 36 Using this method, they could enrich ∼1.6 nm s-SWCNTs consisting of several chiralities, including the (18,4), (19,2), and (20,0) tubes.…”
Section: Density Gradient Ultracentrifugation (Dgu)mentioning
confidence: 99%
“…In the second set of samples the adhesion layer was replaced by Al. Then 1 mg/mL arc discharge CNTs dispersed in 2% (w/v) sodium cholate (SC) were sorted according to the electronic type by applying a two-step density gradient ultracentrifugation (DGU) method. , (For more details see the Supporting Information, section S1.) For sorting of sc-SWCNTs and m-SWCNTs, the solutions had a content of 2% (w/v) sodium dodecyl sulfate (SDS) with SDS–SC ratios of 1/4 and 3/2, respectively.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…For sorting of sc-SWCNTs and m-SWCNTs, the solutions had a content of 2% (w/v) sodium dodecyl sulfate (SDS) with SDS–SC ratios of 1/4 and 3/2, respectively. The semiconducting-to-metal ratios of the unsorted SWCNT dispersion and the collected fractions were determined by UV–vis spectroscopy as described elsewhere. , (See also the Supporting Information, section S1.) The semiconducting enriched SWCNTs were aligned between the palladium electrodes using dielectrophoresis by applying an ac voltage of 5 V pp at 10 MHz for 20 s over the capacitively coupled electrodes.…”
Section: Experimental Sectionmentioning
confidence: 99%